Optimizing Pest Control and Reducing Pesticide Consumption in Citrus Orchards against citrus soft scale, Pulvinaria aurantii Cockerell (Hemiptera: Coccidae) - Amiri-Besheli, Behnam; BELBASI, FATEMEH; Damavandian, Mohammad Reza; Tourani, Amir H. (ENTOMOLOGIA HELLENICA, 2025)
The citrus soft scale, Pulvinaria aurantia Cockerell (Hemiptera: Coccidae), is a major citrus pest. In this study, the efficacy of chlorpyrifos, acetamiprid, and Palizin, both alone and in combination with mineral oils and CitraPlus oils, were investigated against first and second instar nymphs of citrus soft scale under laboratory conditions. Results showed that the combination of acetamiprid with CitraPlus oil exhibited a synergistic effect, resulting in lower dose of acetamiprid required to achieve the same level of control compared to only acetamiprid application. However, in chloropyrifus treatment a dose of 9 ml/L resulted in only 75% mortality of the second nymph stage of P. aurantii. This indicates that P. aurantii now requires higher doses of the insecticide for effective population control. Overall, the findings of this research demonstrated that the combination of mineral oils and CitraPlus oils with pesticides significantly improved their effectiveness while reducing the amount of pesticide needed.